The Effectiveness of Implementing Group Work in the Classroom and Its Benefits in Assessing - Dursunova Jamila Ahmad qizi (International Journal on Integrated Education, 2021)
As we know, multiple use of assessing of the educational process and the use of information and communication technologies can improve the learning process in a very good way. It can develop educational activities and contribute to the objectiveness of the assessment of learning results. The article deals with the issues based on analyzing the efficiency of group work activities in assessing students’ knowledge.